2019
DOI: 10.1515/hf-2018-0251
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanocrystals/silver nanoparticles: in-situ preparation and application in PVA films

Abstract: With the increasing application of polyvinyl alcohol (PVA) films in the field of food packaging, it is important to improve its mechanical and antibacterial properties. This paper focuses on the preparation of PVA nanocomposite films and how their properties are affected by a silver-loaded nanocellulose solution. Cellulose nanocrystals (CNCs) were used as both the carrier and the dispersant of silver nanoparticles (AgNPs) prepared using glucose as the reducing agent. Ag+ was stabilized by the many hydroxyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
(24 reference statements)
3
20
0
Order By: Relevance
“…Standard deviation values highlight a variation in the range of 5-15% from the mean value, highlighting the good repeatability in the tensile properties. These results are coherent with the ones reported by Thiagamani et al [47] for banana peel powder and AgNPs cellulose-based films and by Fan et al [48] for cellulose nanocrystals and AgNPs PVA films.…”
Section: Film Characterizationsupporting
confidence: 92%
“…Standard deviation values highlight a variation in the range of 5-15% from the mean value, highlighting the good repeatability in the tensile properties. These results are coherent with the ones reported by Thiagamani et al [47] for banana peel powder and AgNPs cellulose-based films and by Fan et al [48] for cellulose nanocrystals and AgNPs PVA films.…”
Section: Film Characterizationsupporting
confidence: 92%
“…In this context, both selected polysaccharides, namely ulvan and cellulose nanocrystals (CNC), have been demonstrated to be biocompatible and to have relevant tissue healing properties. Moreover, their use as stabilizing agents of metallic nanoparticles has been recently confirmed, supporting the possible suitability of these macromolecules to be employed as biomaterials [31][32][33][34].…”
Section: Introductionmentioning
confidence: 82%
“…Li Fan and Hui Zhang et al studied the use of CNCs as carriers and stabilizers for AgNPs on polyvinyl chloride nanocomposites ( Figure S4 ). It was found that the AgNPs have been successfully prepared with an average size of 25 nm in spherical form and dispersed uniformly on the surface of CN-like uniform sizes [ 46 ].…”
Section: Cellulose Formsmentioning
confidence: 99%